Genetic Modification of Tumor-Infiltrating Lymphocytes via Retroviral Transduction - Weinstein-Marom, Hadas; Gross, Gideon; Levi, Michal; Brayer, Hadar; Schachter, Jacob; Itzhaki, Orit; Besser, Michal J. (Frontiers in Immunology, 2021)
Adoptive T cell therapy (ACT) holds great promise for cancer treatment. One approach, which has regained wide interest in recent years, employs antitumor T cells isolated from tumor lesions ('tumor-infiltrating lymphocytes' or TIL). It is now appreciated that a considerable proportion of anti-melanoma TIL recognize new HLA-binding peptides resulting from somatic mutations, which occurred during tumor progression. The clinical efficacy of TIL can potentially be improved via their genetic modification, designed to enhance their survival, homing capacity, resistance to suppression, tumor killing ability and additional properties of clinical relevance. Successful implementation of such gene-based strategies critically depends on efficient and reproducible protocols for gene delivery into clinical TIL preparations. Here we describe an optimized protocol for the retroviral transduction of TIL. As the experimental system we employed anti-melanoma TIL cultures prepared from four patients, recombinant retrovirus encoding an anti-CD19 chimeric antigen receptor (CAR) as a model gene of interest and CD19+ and CD19- human cell lines serving as target cells. Transduction on day 7 of the rapid expansion protocol (REP) resulted in 69 ± 8% CAR positive TIL. Transduced, but not untransduced TIL, from the four patients responded robustly to CD19+, but not CD19- cell lines, as judged by substantial secretion of IFN- following co-culture. In light of the rekindled interest in antitumor TIL, this protocol can be incorporated into a broad range of gene-based approaches for improving the in-vivo survival and functionality of TIL in the clinical setting.